2014
DOI: 10.1002/jbio.201300179
|View full text |Cite
|
Sign up to set email alerts
|

Comparative suitability of CFDA‐SE and rhodamine 6G for in vivo assessment of leukocyte‐endothelium interactions

Abstract: Intravital fluorescence microscopy (IVM) is a predestined tool for investigating the fate of leukocytes during the process of leukocyte recruitment. In the present study, the commonly used dye for this purpose, rhodamine 6G, and carboxyfluorescein diacetate succinimidyl ester (CFDA‐SE) were compared for leukocytes labelling with respect to suitability for IVM studies. Their potential in labelling different leukocytes subpopulations as well as their fluorescence intensities were assessed by flow cytometry revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The potential of rhodamine 6G and carboxyfluorescein diacetate succinimidyl ester (CFDA‐SE) in labeling different leukocytes subpopulations as well as their fluorescence intensities were assessed by flow cytometry. CFDA‐SE revealed to be superior in labeling leukocytes for intravital fluorescence microscopy with respect to image quality . Yet, to date, flow cytometry systems have lacked the ability to capture complex fluorescence dynamics due to the transient nature of flowing cells.…”
Section: Cell and Bacteria Characterizationmentioning
confidence: 99%
“…The potential of rhodamine 6G and carboxyfluorescein diacetate succinimidyl ester (CFDA‐SE) in labeling different leukocytes subpopulations as well as their fluorescence intensities were assessed by flow cytometry. CFDA‐SE revealed to be superior in labeling leukocytes for intravital fluorescence microscopy with respect to image quality . Yet, to date, flow cytometry systems have lacked the ability to capture complex fluorescence dynamics due to the transient nature of flowing cells.…”
Section: Cell and Bacteria Characterizationmentioning
confidence: 99%
“…We used 0.05 % Rhodamine 6G for assessment of leukocyte adhesion, rolling and migration across pial brain vessels [ 18 ]. The dye injection technique does affect the outcome of imaging acquisition, leaving the intravenous injection of any labeling agent as the preferable method [ 21 ]. We found that retro-orbital injection was the preferred method for injection of the fluorophore chosen, as has been demonstrated for other compounds that need to be delivered intravenously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…120,126 However, this approach presents limitations as a result of parenchymal tissue accumulation and phototoxic-induced hemodynamic alterations. 127,128 A promising new dye, which apparently avoids these disadvantages, recently was tested for intravital imaging of leukocytes in the liver. 127 Carboxyfluorescein diacetate succinimidyl ester does not compromise leukocyte circulation and recruitment, 129 and in vivo staining of leukocytes showed a high imaging quality of leukocytes.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…127,128 A promising new dye, which apparently avoids these disadvantages, recently was tested for intravital imaging of leukocytes in the liver. 127 Carboxyfluorescein diacetate succinimidyl ester does not compromise leukocyte circulation and recruitment, 129 and in vivo staining of leukocytes showed a high imaging quality of leukocytes. 127 However, carboxyfluorescein diacetate succinimidyl ester has not been used for in vivo imaging of leukocytes in the kidney yet.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%